IDENTIFIKASI KOMPENSASI MANAJEMEN, CAPITAL INTENSITY DAN LEVERAGE TERHADAP TAX AVOIDANCE(Studi Empiris pada Perusahaan Manufaktur yang terdaftar di Bursa Efek Indonesia (BEI) Periode 2016-2018) - Muhammad Alghifari (2021)
This study aims to examine the effect of audit quality on the relationship between executive compensation and capital intensity on Tax Avoidance. In this study, Tax Avoidance was proxied using the Book Tax Differences (BTD). The sample used in this study were 97 manufacturing companies listed on the Indonesia Stock Exchange (BEI). The analysis technique used in this research is panel data regression analysis with a significance level of 5% and uses the STATA 13 application in conducting hypothesis testing. The results in this study indicate that (1) management compensation has an effect on Tax Avoidance. (2) intensity capital has a significant effect on Tax Avoidance. (3) Leverage has a significant effect on Tax Avoidance.